On a human–robot workplace design and task allocation system. Issue 12 (2nd December 2017) - Tsarouchi, Panagiota; Michalos, George; Makris, Sotiris; Athanasatos, Thanasis; Dimoulas, Konstantinos; Chryssolouris, George
Abstract : This paper proposes a method for human–robot (HR) task planning, considering at the same time, the design of the workplace. A model for the representation of humans and robots as a team of active resources is proposed, while equipment such as working tables and fixtures are considered passive resources. The HR workload is structured in a three-level model. A multi-criteria decision-making framework is used for the formulation of alternative layouts and task allocations. Both analytical models and simulation are used for the estimation of the criteria values, allowing for the evaluation of the different alternatives. A software prototype has been implemented and tested in white goods and in automotive industry cases, demonstrating that the tool can identify good quality solutions in a short time frame.